Kemampuan Sumber Daya Manusia Dalam Beraktifitas Pengelolaan Usaha - Fiderius Ismanto Ismanto; Akhmad Nurrofi; Sri Sulistyaningsih (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
MSMEs that are partners in Community Service activities partner with Popcron MSMEs located in Mangunharjo Village, Pulokulon District, Grobogan Regency. The problem faced by Popcorn SMEs is the limited creativity of Human Resources in creativity due to the lack of ability of Human Resources to keep up with technological developments. The activity method that is the solution to partner problems is assistance in the form of training related to social media. This activity is directed at instilling an understanding of the importance of social media for partners so that they can expand the market and increase sales of partner products. Apart from that, mentoring activities related to popcorn product packaging innovation were also carried out, which is an important part of the management effort so that the community is interested in Mr. Ns' MSME products. From this activity it is hoped that it will expand the partner's business market. The result of this dedication is the realization of new packaging, the existence of a business account that can be used as a tool for promotion. Besides that, this service also produces partners' understanding of simple bookkeeping